1967
DOI: 10.1083/jcb.34.3.817
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Myelin Lamellar Structure in the Absence of Lipid

Abstract: The fine structure of myelin was studied in glutaraldehyde-fixed rat sciatic nerves depleted of lipid by acetone, chloroform:methanol (2:1 v/v), and chloroform:methanol:concentrated HC1 (200:100:1, v/v/v). One portion of each of these nerves, plus the extracts, was saponified and analyzed by gas-liquid chromatography for fatty acids. The remainder of each nerve was stained in osmium tetroxide in CC1 4 (5g/100cc) and was embedded in Epon 812. Thin sections, examined in the electron microscope, revealed the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

1969
1969
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(37 citation statements)
references
References 17 publications
2
33
0
2
Order By: Relevance
“…However, myelin may not necessarily form on preexisting lipid bilayers being laid down initially. Myelin basic protein could be the starting foundation around which lipid is laid, an idea given credence by the observation already made by Napolitano et al (22) that myelin retains a lamellar structure in the absence of lipids. It is essential to pursue higher resolution structural analyses of MBP under varied conditions to clarify such issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, myelin may not necessarily form on preexisting lipid bilayers being laid down initially. Myelin basic protein could be the starting foundation around which lipid is laid, an idea given credence by the observation already made by Napolitano et al (22) that myelin retains a lamellar structure in the absence of lipids. It is essential to pursue higher resolution structural analyses of MBP under varied conditions to clarify such issues.…”
Section: Discussionmentioning
confidence: 99%
“…In the earliest stage of these lesions, the storage cells are electron microscopically similar to those seen in the genetic mucopolysaccharidoses and infantile GG. With progression of the lesions, the characteristic curvilinear tubular structures which are considered to be ultrastructural expression of ceramide accumulation (5,6,18) (8,22) have explained that the width of the clear osmiophobic layers is almost compatible with estimates of the length of the ceramide portion of sphingomyelin and that the osmiophilic layers may correspond to phosphoryl choline, while others have speculated that accumulation of sphingomyelin, cholesterol or a certain other lipid occurs in the interstices of the lamellae made up of proteins (4,16). To obtain precise knowledge about what kinds of compounds constitute the myelin-like figures, further correlative electron microscopical and biochemical studies will be required, but the fact that loosening of concentric lamination and vacuolar alteration of the inclusions were observed in Niemann-Pick cells stored with excess of cholesterol may indicate that cholesterol deposition occurs in the interstices of the lamellae (28) .…”
Section: Discussionmentioning
confidence: 99%
“…These configurations are observed only after certain fixation schedules, usually those employing glutaraldehyde and/or osmium tetroxide (Napolitano et al 1967, Pontefract et al 1969, Silva 1966, Thomas and Isaac 1967, but are not reported after fixation with potassium permanganate (e. g., Bracker 1968). It has been suggested that fixation with glutaraldehyde and/or osmium tetroxide "preserves" these structures (Napolitano et al 1967, Silva 1966, and alternatively, that these configurations are fixation artifacts (Olah and Rohlich 1966).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that fixation with glutaraldehyde and/or osmium tetroxide "preserves" these structures (Napolitano et al 1967, Silva 1966, and alternatively, that these configurations are fixation artifacts (Olah and Rohlich 1966). These configurations are often observed in old or degen erating cells (Carbonell and Pollak 1962) , or at sites of autolysis, leading to the suggestion that the configurations are formed from the remaining water and lipid after the loss of cellular protein (Swift and Hruban 1964) .…”
Section: Introductionmentioning
confidence: 99%